Vulnerabilidad sísmica del edificio residencial Los Armijos ubicado en cantón Pasaje – El oOro - Espinoza Moran, Dayana Milena (2024)
In Ecuador there are a large number of buildings and other constructions that do not meet Ecuadorian construction standards, therefore the effort to improve the quality of buildings should be the priority. Several large earthquakes have occurred in the country that have left countless human and economic losses. In 2023, an earthquake occurred that affected the city of Pasaje where most of the buildings are old and have not been built without structural criteria, which caused most of the structures to collapse or have cracks. Based on the risk history, the investigative process was developed with the purpose of evaluating the seismic vulnerability of the “Los Armijos” residential building; The physical plans were captured in the AutoCAD program to have the digital data. Additionally, the SHELL and SAP 2OOO programs were used to carry out the survey and evaluation. The structural condition of the “Los Armijos” building presents problems in high periods that do not comply with the minimum limits already regulated in the NEC15 and has low frequencies in high periods, therefore it is a flexible structure. The 3 modal deformations of the building were developed.